Sideways stories from Wayside School - Sachar, Louis, 1954-; Brinckloe, Julie (New York : Avon Books, 1985)
Presents humorous episodes from the classroom on the thirtieth floor of Wayside School, which was accidentally built sideways with one classroom on each story.
Book Links (A.L.A.)
Elem. School Library Collection
Kliatt
Book Links (A.L.A.), July 2006
Elem. School Library Collection, June 2000
Kliatt, March 2005
Keywords: Humorous stories; Schools -- Fiction; Humorous fiction; School stories